SYNTHESIS OF A SUB-OPTIMAL DIGITAL TRACKING SYSTEM WITH INDIRECT COMMUNICATION ON THE GASKET IMPACT - Zhitetsky , L. S.; Sushchenko, O. A.; Golota, A. N.; Artasyuk , Yu.A. (Problems of Informatization and Control, 2021)
The article solves the problem of structural-parametric synthesis of a digital tracking system, based on the use of the procedure for evaluating the future values of the unmeasurable reference action. The simulation results are presented.